Analysis of the Effect of Crystal form on Precipitated Calcium Carbonate (PCC) of Dead Coral Reefs with the Addition of HNO3 Concentration - Meilianti; Nofiansah; Rizki, Dea Ayu Tri (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Many dead coral reefs found on the coast have not been treated optimally and currently their use is still limited as decoration in aquariums. Coral reefs contain calcium carbonate, silicon dioxide, sodium oxide, magnesium peroxide, and Iron (III) oxide, with a calcium carbonate content of around 73.76%. Because of its high calcium carbonate content, it can be used as a raw material for making PCC (Precipitated Calcium Carbonate) which is widely used in the industrial, health and food sectors. The aim of this research is to obtain the optimal temperature and time for CaO levels, as well as the effect of nitric acid solution concentration on the yield with a high level of purity in PCC products using the carbonization method. The fixed variables are: coral reef mass, independent variables: temperature, calcination time and nitric acid concentration and dependent variables: CaO yield and CaCO3 levels. The calcination temperature used was 700℃, 750℃, 800℃, 850℃, 900℃ and HNO3 concentration 1.50M, 2.00M, 2.50 M, 3.00M, 3.50M with Ca analysis using AAS and PCC morphology and content using SEM-EDX. Optimal conditions are the results of calcination at a temperature of 900℃ with an HNO3 concentration of 3.50 M resulting in a yield of 76% with a purity of 98.58%, pH 8, white with a Ca concentration (ppm) of 1,962,630 and the crystal form obtained at 3.00 M HNO3 is calcite and 3.50 M HNO3 is vaterite.